RESEARCH ON REVERSE OSMOSIS SEPARATIONOF PROCESS SOLUTIONS FOR CORN STARCH PRODUCTION - Kovaleva O.A.; Lazarev S.I. (Техника и технология пищевых производств)
The article deals with the problem of reducing the cost of corn starch by separating technological solutions using the method of reverse osmosis. Shown is the purpose of the experimental work; objects and methods of the research are presented, a scheme of the pilot unit and the design of its basic element - the membrane device with flat intermembrane channels, and the principle of its operation are given. The membrane device can effectively separate the technological solutions of starch-treacle production. We have studied such factors as hydrodynamic permeability and the rejection rate through the membranes of MGA-100 and OPM-K when separating technological solutions of corn starch production at ОАО Hobotovskое plant «Krakhmaloprodukt». Graphic dependences of hydrodynamic permeability and the rejection rate on substance concentration in the original technological solution of starch-and- treacle production when using semipermeable membranes of MGA-100 and OPM-K are presented. It is shown that the membrane of OPM-K type has a maximum hydrodynamic permeability during the process of reverse osmosis under the same experimental conditions (temperature, pressure, the membrane working area, etc.). The obtained data on the separation of technological solutions of corn starch production using the MGA-100 and OPM-K membranes allow us to conclude that the use of reverse osmosis makes it possible to perform a closed technological process, clean water being used only for washing the starch. All other operations use the return water. Cleaning the solutions of starch-treacle production will enable using the minimum amount of water for technological processes. As a consequence, the charges constituting a significant proportion in corn starch cost will be reduced.